Estandarización de procesos en línea de prendas piratas en empresa artesanal de confecciones textiles - Ponce Polo, Kevin Jonathan (2020)
This project consists of a proposal to improve the production processes of the artisan company Ecofibra, in its line of star products that consist of a pirate style costume. This proposal is made through the standardization of the processes involved in the manufacture of star products, saving transportation costs, increasing production and improving the quality of work. To start this work, an analysis of the current situation of the company was carried out in order to obtain real and current information about what is happening inside the facilities. A data collection was carried out on the processes of each star product where it was possible to identify the daily production capacity for blouses (96), shirts (87), skirts (112), pants (172), times not established in each activity, separate work team, allocation of ineffective loads and unnecessary displacements. In stage the work study methodology was applied to standardize the productive processes. The proposal starts from the analysis of the current situation and consists of the measurement of the work for each activity and each star product that is made, to subsequently make the real daily production that can be produced. The real production of garments that the company can produce, with established times, increased by 26.25 percent. Likewise, a new distribution of machinery was carried out at the plant to reduce movement times and distances between activities, saving 82.25 percent. On the other hand, load distribution standardizes the activities that each operator must perform. Finally, organizational measures are proposed in the cellar to support the production processes. Finally, the capacity managed within the company and the current movements were compared with the proposals for improvement through standard times and new plant distribution. The result was the increase the production of blouses by 8 percent, shirts 40 percent, skirts 12 percent and pants 11 percent. This for the company reflects an increase in its annual profit of USD 51,489.39.